Effect of borax on the hydration and setting of magnesium phosphate cements. (19th September 2022) - Gelli, Rita; Tonelli, Monica; Martini, Francesca; Calucci, Lucia; Borsacchi, Silvia; Ridi, Francesca
Graphical abstract: Highlights: Borax effect on the hydration of magnesium phosphate cements was studied. The setting was investigated with Gillmore tests, calorimetry, Raman and pH analyses. Set cements were studied with XRD, SEM, mechanical tests and Solid State NMR. Borax prolongs the setting time and reduces the heat released during setting. Retarding action is due to the interaction between borates and Mg 2+ and NH4 + . Abstract: This work unravels for the first time the concentration dependent retarding effect of borax on tri-magnesium phosphate-based cements by studying the hydration and the phases formed in the set cements, exploiting multiple characterization techniques. In the presence of borax, the hydration was found to be slower and less exothermic, leading to the formation of struvite without newberyite, with no effect on cement's strength. The observed boron species allowed us to ascribe the retardation to the complexation of NH4 + and Mg 2+ by borate and polyborate anions.